Regression Analysis and Forecasting with Regression Model in Economics - Kumar, Nand Kishor; Shah, Raj Kumar; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2025)
This work aims to provide a mathematical model that can be applied to prediction and defines this relationship. It helps economists understand how different factors influence economic indicators such as GDP, inflation, unemployment, and market trends. Forecasting using regression models provides valuable insights for policy-making, business strategies, and economic planning.